1988
DOI: 10.1085/jgp.92.3.331
|View full text |Cite
|
Sign up to set email alerts
|

Removal of inactivation causes time-invariant sodium current decays.

Abstract: The kinetic properties of the closing of Na channels were studied in frog skeletal muscle to obtain information about the dependence of channel closing on the past history of the channel. Channel closing was studied in normal and modified channels. Chloramine-T was used to modify the channels so that inactivation was virtually removed. A series of depolarizing prepulse potentials was used to activate Na channels, and a -140-mV postpulse was used to monitor the closing of the channels. Unmodified channels decay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

1988
1988
1991
1991

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 18 publications
(24 reference statements)
4
23
0
Order By: Relevance
“…Depending upon the size of k6 + k7 compared to the eigenvalues of the system, the delay may not be experimentally perceptible. Experimental removal of inactivation using chloramine-T is equivalent to making k5 = k6 = k7 = 0 which will eliminate the third exponential coefficient; thus in this case, the predicted channel closing will remain biexponential after inactivation removal consistent with previously reported observations (Hahin, 1988).…”
Section: Conditions For Physical Realizabilitysupporting
confidence: 83%
See 4 more Smart Citations
“…Depending upon the size of k6 + k7 compared to the eigenvalues of the system, the delay may not be experimentally perceptible. Experimental removal of inactivation using chloramine-T is equivalent to making k5 = k6 = k7 = 0 which will eliminate the third exponential coefficient; thus in this case, the predicted channel closing will remain biexponential after inactivation removal consistent with previously reported observations (Hahin, 1988).…”
Section: Conditions For Physical Realizabilitysupporting
confidence: 83%
“…Recent experiments (Hahin, 1987;Hahin, 1988) have shown that the properties of Na current tails in frog skeletal muscle are consistent with the predictions of Markov models. Using Markov models to obtain predictions of the expected kinetics of the decay as a function of the duration of the pulse used to activate the Na channels, it is possible to evaluate possible alternative models to describe the observed tails of current.…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations